Improvement proposal to achieve shrinkage reduction in home dispatch process in retail company - Pimentel Piscoya, Alison Maire (2024)
In this research the problem is the generation of wastage in the home dispatch (HD) process and in the reverse logistics of a retail sector company, so its main objective will be to reduce them. The DMAIC methodology was used for process improvement. The engineering tools used correspond to Lean Six Sigma such as process standardization and Poka Yoke. After simulating the improvement proposal with the Arena software, the main results obtained were, at 95% confidence, the reduction in the number of reentries, wastage, and absenteeism, as evidenced by the decrease in the confidence interval limits. For the quantity of reentries indicator, the simulated improvement yields a confidence interval of [43.7081 ; 49.8239] units of product re-entered, resulting in values lower than those obtained in the current situation, according to its confidence interval [99.7428 ; 111.3172] units of product re entered. For the quantity of wastage indicator, the simulated improvement yields an approximate confidence interval of [6.3968 ; 8.8032] units of product wasted, resulting in lower values than those obtained in the current situation, according to its confidence interval [21.4576 ; 25.8744] units of product wasted. For the number of absent customers indicator, the simulated improvement yields an approximate confidence interval of [2.5717 ; 4.0949] absent customers, resulting in values lower than those obtained in the current situation, according to its confidence interval [31.1758 ; 37.1562] absent customers.